Onthophagus fragosus n.sp. a second endemic species of Onthophagus Latreille from Cuba (Coleoptera : Scarabaeidae, Scarabaeinae) - Génier, François; Howden, Henry F. (Zootaxa, 2014)
Onthophagus fragosus, a new species of Onthophagus, is described from Cienfuegos Province on the island of Cuba. Specimens were collected in leaf litter samples at elevations of 650-935 m. It appears to be most closely related to O. marginatus Castelnau, the only other Cuban endemic Onthophagus species. Images of habitus and of male genitalia are provided.